Transforming Adolescent Health Monitoring: Implementing the e-Rapor Sehatku in Puskesmas Bojong Rawalumbu - Dewanti, Lintang Purwara; Sitoayu, Laras; Melani, Vitria; Fanani, Lutfi (TRIMAS: Jurnal Inovasi dan Pengabdian Kepada Masyarakat, 2024)
Regular health screenings in schools are vital for fulfilling the health rights of Indonesian children. However, the current manual health report cards are inefficient and time-consuming. This community service project aims to address this by developing and implementing a digital health report card, e-Rapor Sehatku, at the Bojong Rawalumbu Community Health Center (Puskesmas). This initiative, targeting the Nutrition Implementing Staff (TPG) at Puskesmas Bojong Rawalumbu, involves collaboration between the fields of Nutrition Science and Information Technology. The project includes needs analysis through in-depth interviews and FGD with key stakeholders, application development, and pilot testing. Training for TPG covers data input, processing, presentation, interpretation, and conclusion drawing using the e-Rapor Sehatku application. The project began with securing permissions from the Bekasi City Health Office in June 2023. Activities carried out include needs analysis, application design and development, and initial application testing. The needs analysis revealed a strong demand for a digital health reporting system, prompting the development of e-Rapor Sehatku. Initial trials with TPG highlighted several functional issues, leading to subsequent refinements and a small class trial. The project successfully identified the need for digital health reporting and developed the e-Rapor Sehatku application. Initial trials provided valuable feedback for further refinement. The next steps involve conducting broader user trials within the school community to ensure comprehensive implementation. The implementation of e-Rapor Sehatku at Puskesmas Rawalumbu is expected to facilitate regular, efficient, and systematic health screenings, ultimately improving children's health. The digital health report will also enhance communication between parents and teachers, promoting greater parental involvement in their children's health.